Stockholm [ the making of a metropolis - Hall, Thomas , 1939-; Rèorby, Martin (Planning, history and environment, 2009)
"In this unique study of the Swedish capital, Thomas Hall focuses on the phases of development which shaped the Stockholm of the twenty-first century, and whose impacts can be clearly read in today's urban environment, often interwoven with each other." "Following the emergence of the medieval city in the thirteenth century, the first major extension of the city in the mid-seventeenth century sought to transform Stockholm into the 'Paris of the North'. For two hundred years development was unremarkable until the Lindhagen plan of 1866 set out to create a healthier, more beautiful, better functioning, and much larger city. The next phases in the city's development saw the consolidation of the city centre and the coming of the suburbs, but it was reconstruction of Stockholm city centre in the 1950s and 1960s that must surely be one of Europe's largest and most radical urban development projects. Finally, the densification process that characterized the last decades of the twentieth century and the start of the twenty-first, revealed a radical change in the architectural idiom in the city - the breakthrough of postmodernism."--Jacket.